Gambaran Faktor-Faktor Pendorong Perilaku Pengelolaan Sampah Rumah Tangga Pada Warga Di Kawasan Kayu Tiga Cekdam Kecamatan Sirimau Kota Ambon - Arfan Ohorella; M Fadly Kaliky (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2023)
According to the World Health Organization (WHO, 2006) waste is something that is not used, not used, not liked or something that is discarded that comes from human activities and does not occur by itself. The issue of waste in Ambon City has become a serious problem, because the volume of waste generated in Ambon City is 220 tons per day. Meanwhile, the waste transportation capacity that can be carried out by janitors is only 160 tons per day. This limited transport capacity will greatly affect the system and capacity of conventional waste management at the Integrated Waste Management Installation (IPST) in the Toisapu Ambon area. This study aims to determine the description of knowledge, attitudes, and community actions related to household waste management in the Kayu Tiga Cekdam Area, Sirimau District, Ambon City. The type of research used was descriptive survey, the population was 77 households (head of family), the sample was 77 households, the sample was taken using total sampling technique. Direct data collection, instrument The research used is a questionnaire, the data is processed manually and assisted by a computer, and the data obtained is presented in text and table form. The results of the study can be seen that the highest knowledge variable 33 (62%) is categorized as good, the highest attitude variable 27 (51%) is categorized as not good and the highest action variable 33 (62%) is categorized as not good. Based on the results of research conducted in the Kayu Tiga Cekdam Area, Sirimau District, Ambon City, it can be concluded that the knowledge behavior of 33 households (62%) is in the good category, the attitude behavior of 27 households (51%) is in the bad category and the action behavior of 33 households (62%) is in the bad category.